Two Strains of Crocosphaera watsonii with Highly Conserved Genomes are Distinguished by Strain-Specific Features - Bench, Shellie R.; Ilikchyan, Irina N.; Tripp, H J.; Zehr, Jonathan P. (Frontiers in Microbiology, 2011)
Unicellular nitrogen-fixing cyanobacteria are important components of marine phytoplankton. Although non-nitrogen-fixing marine phytoplankton generally exhibit high gene sequence and genomic diversity, gene sequences of natural populations and isolated strains of Crocosphaera watsonii, one of two most abundant open ocean unicellular cyanobacteria groups, have been shown to be 98-100% identical.. The low sequence diversity in Crocosphaera is a dramatic contrast to sympatric species of Prochlorococcus and Synechococcus, and raises the question of how genome differences can explain observed phenotypic diversity among Crocosphaera strains. Here we show, through whole genome comparisons of two phenotypically different strains, that there are strain-specific sequences in each genome, and numerous genome rearrangements, despite exceptionally low sequence diversity in shared genomic regions. Some of the strain-specific sequences encode functions that explain observed phenotypic differences, such as exopolysaccharide biosynthesis. The pattern of strain-specific sequences distributed throughout the genomes, along with rearrangements in shared sequences is evidence of significant genetic mobility that may be attributed to the hundreds of transposase genes found in both strains. Furthermore, such genetic mobility appears to be the main mechanism of strain divergence in Crocosphaera which do not accumulate DNA microheterogeneity over the vast majority of their genomes. The strain-specific sequences found in this study provide tools for future physiological studies, as well as genetic markers to help determine the relative abundance of phenotypes in natural populations.